A Kinect™ camera based navigation system for percutaneous abdominal puncture. (12th July 2016) - Xiao, Deqiang; Luo, Huoling; Jia, Fucang; Zhang, Yanfang; Li, Yong; Guo, Xuejun; Cai, Wei; Fang, Chihua; Fan, Yingfang; Zheng, Huimin; Hu, Qingmao
Abstract: Percutaneous abdominal puncture is a popular interventional method for the management of abdominal tumors. Image-guided puncture can help interventional radiologists improve targeting accuracy. The second generation of Kinect ™ was released recently, we developed an optical navigation system to investigate its feasibility for guiding percutaneous abdominal puncture, and compare its performance on needle insertion guidance with that of the first-generation Kinect ™ . For physical-to-image registration in this system, two surfaces extracted from preoperative CT and intraoperative Kinect ™ depth images were matched using an iterative closest point (ICP) algorithm. A 2D shape image-based correspondence searching algorithm was proposed for generating a close initial position before ICP matching. Evaluation experiments were conducted on an abdominal phantom and six beagles in vivo . For phantom study, a two-factor experiment was designed to evaluate the effect of the operator's skill and trajectory on target positioning error (TPE). A total of 36 needle punctures were tested on a Kinect ™ for Windows version 2 (Kinect ™ V2). The target registration error (TRE), user error, and TPE are 4.26 ± 1.94 mm, 2.92 ± 1.67 mm, and 5.23 ± 2.29 mm, respectively. No statistically significant differences in TPE regarding operator's skill and trajectory are observed. Additionally, a Kinect ™ for Windows version 1 (Kinect ™ V1) was tested with 12 insertions, and the TRE evaluated with the Kinect ™ V1 is statistically significantly larger than that with the Kinect ™ V2. For the animal experiment, fifteen artificial liver tumors were inserted guided by the navigation system. The TPE was evaluated as 6.40 ± 2.72 mm, and its lateral and longitudinal component were 4.30 ± 2.51 mm and 3.80 ± 3.11 mm, respectively. This study demonstrates that the navigation accuracy of the proposed system is acceptable, and that the second generation Kinect ™ -based navigation is superior to the first-generation Kinect ™, and has potential of clinical application in percutaneous abdominal puncture.